1978
DOI: 10.1084/jem.147.3.656
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of anti-Ia alloantisera. I. Elimination of specific suppression by in vivo administration of antisera specific for I-J controlled determinants.

Abstract: The helper and suppressor regulatory activities exerted on antibody responses by T lymphocytes are associated with subregions of the I region of the murine H.2 (major histocompatibility) complex. Using antisera defining Ia antigens, raised by immunization between congenic pairs of mice differing at the ! region, specific suppressor T cells (1, 2) and their soluble and mediators (3-5)have been shown to bear I-J subregion coded determinants, whereas certain helper (enhancing) factors and possibly helper cells po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In particular the I-J gene(s) do not appear to be typical of other class II histocompatibility genes. Nevertheless, despite present uncertainties concerning the physiological role of I-J (14), there is sound experimental evidence demonstrating that anti-I-J antibodies can be used to abrogate Ts function selectively without influencing the activities of other T-cell subsets (15,16). Thus, the demonstration here of increased susceptibility of anti-I-J-exposed mice to the induction of autoimmunity is consistent with a central role for Ts in mediating selftolerance.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…In particular the I-J gene(s) do not appear to be typical of other class II histocompatibility genes. Nevertheless, despite present uncertainties concerning the physiological role of I-J (14), there is sound experimental evidence demonstrating that anti-I-J antibodies can be used to abrogate Ts function selectively without influencing the activities of other T-cell subsets (15,16). Thus, the demonstration here of increased susceptibility of anti-I-J-exposed mice to the induction of autoimmunity is consistent with a central role for Ts in mediating selftolerance.…”
supporting
confidence: 59%
“…Ts can be distinguished from other T-cell subsets by the fact that they carry the serologically defined I-J determinant (11) and, thus, can be selectively removed by antibodies with anti-I-J specificity (16 immunized with a single intraperitoneal injection of 2 x 10' normal RRBC which carry not only rat-specific antigens but also determinants with cross-reactivity for mouse erythrocytes (MRBC) as well (17). Blood was collected at intervals thereafter for measurement of antibodies to MRBC and RRBC.…”
Section: Experimental Model For Eliminating T During Embryonicmentioning
confidence: 99%
“…These findings were subsequently confirmed by Theze et al (9) for a poly(GluU~'l'yrt'~)(GT)-specific TsF and by Greene et al (10) for an azobenzene arsonate-specific TsF. Pierres et al (11,12) demonstrated that the administration of microliter quantities of anti-I-J serum to GT-suppressor strain mice allowed them to make a GT-specific antibody response apparently due to the elimination or inactivation of I-J-bearing Ts. Likewise, Greene et al (13) showed that alloanti-I-J, when administered to S1509a fibrosarcoma-bearing mice, caused regression of the tumor due to the inactivation of tumor-induced Ts.…”
supporting
confidence: 75%
“…Adult thymectomy (12), treatment with a low dose of cyclophosphamide (13), and administration of antisera directed at I-J region coded determinants of the murine major histocompatibility complex (10,11,14) have been used to selectively diminish suppressor T-cell activity. The reasons for the effectiveness of these procedures stems from the fact that the population of thymus-derived lymphocytes can be differentiated into subsets of cells, each subgroup sharing unique biological functions, cell-surface phenotypes, or physiological characteristics (15 We have previously demonstrated that in vivo administration of anti-I-J serum eliminates suppressor T-cell activity in two independent systems (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…The antisera used in this study were raised in the following strain combinations: anti-Iad, (C3H X LG/ckc)F1 anti-C3H.OH; anti-I-Jk, [B1O.A(3R) X DBA/2]F1 anti-B1O.A(5R); and A anti-I-J3 (3R X 9R)F1 anti-B1O.HTT. The specificity and titer of the sera, including control absorption studies and the protocol for intravenous administration of antisera, were as described (10,11 Table 1, the numbers of Dnp-specific clones expressed in the antisera obtained from thymectomized animals are significantly greater than the numbers of anti-Dnp antibody-producing clones expressed in antisera from control mice in both primary and secondary antibody responses to Dnp-GLA or Dnp-GLL. The increased anti-Dnp antibody heterogeneity of antiDnp-GLA or anti-Dnp-GLt antisera of thymectomized animals is noted even though the antigen-binding capacities of the antisera from thymectomized animals are not significantly greater than the antigen-binding capacities of respective antisera from control mice.…”
mentioning
confidence: 99%